Modelling the performance of wind energy conservation system at potential wind farm sites in Kerala - DHANMON FRANCIS YOUNUS A; Dr. Geetha Sussan Philip (Guide) (Tavanur 2013 Department of Farm Power Machinery and Energy)
Modelling the performance of wind energy conservation system at potential wind farm sites in Kerala
Modelling the performance of wind energy conservation system at potential wind farm sites in Kerala